Boronic Acid Transition State Inhibitors Active against KPC and Other Class A β-Lactamases: Structure-Activity Relationships as a Guide to Inhibitor Design - Rojas, Laura J. (Antimicrob Agents Chemother, 2016)
Boronic acid transition state inhibitors (BATSIs) are competitive, reversible β-lactamase inhibitors (BLIs). In this study, a series of BATSIs with selectively modified regions (R1, R2, and amide group) were strategically designed and tested against representative class A β-lactamases of Klebsiella pneumoniae, KPC-2 and SHV-1. Firstly, the R1 group of compounds 1a to 1c and 2a to 2e mimicked the side chain of cephalothin, whereas for compounds 3a to 3c, 4a, and 4b, the thiophene ring was replaced by a phenyl, typical of benzylpenicillin. Secondly, variations in the R2 groups which included substituted aryl side chains (compounds 1a, 1b, 1c, 3a, 3b, and 3c) and triazole groups (compounds 2a to 2e) were chosen to mimic the thiazolidine and dihydrothiazine ring of penicillins and cephalosporins, respectively. Thirdly, the amide backbone of the BATSI, which corresponds to the amide at C-6 or C-7 of β-lactams, was also changed to the following bioisosteric groups: urea (compound 3b), thiourea (compound 3c), and sulfonamide (compounds 4a and 4b). Among the compounds that inhibited KPC-2 and SHV-1 β-lactamases, nine possessed 50% inhibitory concentrations (IC(50)s) of ≤600 nM. The most active compounds contained the thiopheneacetyl group at R1 and for the chiral BATSIs, a carboxy- or hydroxy-substituted aryl group at R2. The most active sulfonamido derivative, compound 4b, lacked an R2 group. Compound 2b (S02030) was the most active, with acylation rates (k(2)/K) of 1.2 ± 0.2 × 10(4) M(−1) s(−1) for KPC-2 and 4.7 ± 0.6 × 10(3) M(−1) s(−1) for SHV-1, and demonstrated antimicrobial activity against Escherichia coli DH10B carrying bla(SHV) variants and bla(KPC-2) or bla(KPC-3) and against clinical strains of Klebsiella pneumoniae and E. coli producing different class A β-lactamase genes. At most, MICs decreased from 16 to 0.5 mg/liter.